Comparative Effects of Processing on Nutritional Compositions of Chickpea (Cicer arietinum) Flour, and Resultant Implications on Histology of Albino Rats - Lawal, Rasheed Tunde; Oyeleke, Gboyega Oluwaseun; Aborisade, Wakili Tope; Odedeji, Joshua Oluremi; Ishola, Abdul Dimeji; Olayiwola, Abdulwasiu Temitope (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This research examined the effects of autoclaved, cooked, and uncooked chickpea flour on animals with uncooked chickpea flour, commercial feed, and basal diets serving as comparisons and histological examination. The seeds of Cicer arietinum were sorted, washed, and sun-dried. The 30 kg of chickpeas were milled into powder using a blender. Three (3) 700 g portions of the powder were separated and placed in a sterile container. The fraction of chickpea flour was autoclaved for 15 minutes and cooked for 1 hour. The mineral and vitamin analysis of autoclaved, cooked, and uncooked chickpea flour was carried out using standard analytical methods. Standard procedures were used to prepare the animal tissue. The results showed that odium ranges from 15.90 to 19.19 mg/kg, potassium from 24.40 to 26.10 mg/kg, magnesium from 2.72 to 4.63 mg/kg, calcium from 3.97 to 5.33 mg/kg, and iron from 0.19 to 0.23 mg/kg in terms of mineral composition, while vitamin analysis ranges from vitamin A, 465.71 +9.27 to 1146.75 +5.63 Unit/g, vitamin B, 0.02 + 0.01, to 0.06 + 0.00 mg/g, and vitamin C, 0.15 + 0.00 to 0.25 + 0.00 mg/g. Raw chickpea flour's mineral and vitamin content was lower than that of cooked and autoclaved chickpea flour. Histological examination reveals that the experimental animals given cooked chickpea flour did not experience any changes in liver histoarchitecture. From this study, it could be concluded that animal consumption of cooked chickpeas could be safe, as it had no negative effects on their liver histology.